El criterio de agregación de valor en los procesos de reorganización empresarial de la ley 1116 de 2006 (2018)
The reorganization processes created by Law 1116 of 2006, constitute a truly valuable measure to economically recover those companies in a crisis situation, and can be considered viable again, under the criterion of value aggregation, as ordered in the first article of Law 1116 of 2006,however, today does not apply the aforementioned criterion, and it is evident the ignorance of the meaning of the concept of value in this part of the norm, and how it is added in these recovery processes.Therefore, the purpose of this study is to provide regulatory effectiveness to that part of the first article of insolvency law 1116 of 2006, providing new knowledge within the field of bankruptcy law, bringing tools and concepts from the financial field, which allow us to understand what is the value of their aggregation as a criterion of mandatory compliance during the business reorganization processes.